2007
DOI: 10.1080/13504850500425949
|View full text |Cite
|
Sign up to set email alerts
|

On the welfare cost of inflation in Europe

Abstract: This article follows Lucas (2000) and Serletis and Yavari (2005) and estimates the welfare cost of inflation in the Euro zone. It uses recent advances in the field of applied econometrics to estimate the interest elasticity of money demand and reports that the welfare cost of inflation is lower in big countries than it is in small countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Perhaps unsurprisingly, this stimulated a considerable amount of further research on the welfare cost of inflation (e.g. Attanasio et al ., ; Serletis and Yavari, , ; Ireland, ; Calza and Zaghini, , ; Cysne and Turchick, ). This further research has generated a number of welfare cost estimates, although none are as high as that reported in Lucas ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps unsurprisingly, this stimulated a considerable amount of further research on the welfare cost of inflation (e.g. Attanasio et al ., ; Serletis and Yavari, , ; Ireland, ; Calza and Zaghini, , ; Cysne and Turchick, ). This further research has generated a number of welfare cost estimates, although none are as high as that reported in Lucas ().…”
Section: Resultsmentioning
confidence: 99%
“…Estimates based on data from other countries are also lower than that found in the influential Lucas () study. For example, Serletis and Yavari () study seven Eurozone countries over the period 1960–2000 and report estimated gains from reducing inflation by 5 percentage points in the range of 0.1 per cent GDP in France to 0.5 per cent GDP in Ireland. Yet lower estimates have been found by, for example, Attanasio et al .…”
Section: Calculating the Welfare Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Ireland (2009 finds the estimated η for the period 1980-2006 to be 0.087. Serletis and Yavari (2007) and Kimbrough and Spyridopoulos (2012) find the estimated elasticities to lie between 0.1 and 0.55 in several European countries. Notes: π t and i t are inflation rate and interest rate at month t, respectively.…”
Section: Interest Rate and Money Demandmentioning
confidence: 95%
“…Using the same approaches of calculating welfare cost of inflation as in Serletis and Yavari (2003), they show that lowering the interest rate from 14% to 3% yield a benefit of about 0.4% of income. Same analysis was extended in Serletis and Yavari (2007) to calculate direct cost of inflation for seven European countries, Ireland, Australia, Italy, Netherlands, France, Germany, and Belgium. The welfare cost estimates of these countries showed that the cost is not homogeneous across these countries and is related to the size of the economy.…”
Section: The Welfare Cost Of Inflationmentioning
confidence: 99%